ANALISIS DETERMINAN RETURN SAHAM SUB SEKTOR OTOMOTIF DAN KOMPONEN DI BURSA EFEK INDONESIA - Natasha Miftahuljanah (2022)
This study aims to analyze the effect of profitability using return on assets, Leverage using debt to equity ratio proxies, market value using price earning ratio proxies and exchange rates on stock returns. The population of this study were the Automotive and Component companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. By using a saturated sample and 12 companies in the Automotive and Components sector with a period of 5 years of research obtained 60 sample units. Hypothesis testing in this study uses panel data regression using the E-views 12 program and the significant value used is 5%. The test results show (1) profitability has no effect on stock returns, (2) leverage has no effect on stock returns, (3) market value has a positive effect on stock returns and (4) the exchange rate has no effect on stock returns.